Optimalisasi Reccess Time Melalui Instant Activity Terhadap Tingkat Aktivitas Fisik dan Kemampuan Motorik Kasar pada Siswa Sekolah Dasar - Mochamad Anfaza Davaras Ismail; Yogi Akin; Wildan Alfia Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine and analyze the effect of implementing instant activity during recess time on improving gross motor skills of elementary school students. This study uses an experiment with a quantitative approach. The sample consists of fifth and sixth grade students aged 11-12 years and fourth grade students aged 9-10 years at SDN 065 Cihampelas who were selected using purposive sampling techniques. The research instrument used was PAQC (Physical Activity Questionnaire for Children) to measure children's physical activity and then TGMD (Test of Gross Motor-Second Edition) to measure children's gross motor skills. The results of the study showed that the average value of physical activity at SDN 065 Cihampelas was 2.34 in the pretest while the average value of the posttest was 2.66. While in the locomotor pretest the mean value was 40.62 while the locomotor posttest value was 43.95. While in the control object pretest the average value was 39.85 while the average value in the control object posttest was 44.17. Based on the paired t-test, there was a difference between before and after treatment. It can be concluded that there is a significant difference in the ability to optimize reccess time through instant activity on the level of physical activity and gross motor skills in elementary school students. Keywords: Elementary School Students, Gross Motor Skills, Instant Activity Physical Activity, Recess Time